Inovasi Pembelajaran: Media Diorama Untuk Peningkatan Kosakata Bahasa Inggris di Mi Fathul Jannah - Hesty Widiastuty; Nazwa Maulani Dewi; Siti Nurrahmah; Yulis Setiawati; Muhammad Hidayatur Rahman; Ayu Putriana Lestari; Ahmad Basahil (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
In the current globalized world, learning English is essential for teachers and students in Indonesia to develop effective teaching strategies. Engaging edducational media, like diorama, can increase students' comprehension and focus when learning English. This community outreach is being carried out at MI Fathul Jannah to promote the use of dioramas in English language instruction. The method that is used is called